Serum Levels of IL-17 and IL-23 in Patients With Rheumatic Mitral Stenosis. Issue 18 (May 2016) - Bilik, Mehmet Zihni; Kaplan, İbrahim; Polat, Nihat; Akil, Mehmet Ata; Akyüz, Abdurrahman; Acet, Halit; Yüksel, Murat; İnci, Ümit; Kayan, Fethullah; Toprak, Nizamettin
Abstract : Abstract: Rheumatic mitral valve stenosis (RMS) is a complication of rheumatic heart disease (RHD) and leads to significant morbidity and mortality. RHD is a chronic inflammatory and autoimmune disease that is associated with cytokine activities. The etiology of RMS is not fully understood yet. Interleukin (IL)-17 and IL-23 have a key role in development of the autoimmunity. The expression of these cytokines in RMS remains unclear. In this study, we investigated the serum levels of IL-17 and IL-23 in RMS patients compared to healthy subjects. A total of 35 patients admitted to cardiology outpatient clinic between December 2014 and May 2015 who were diagnosed with RMS formed the study group. Age- and gender-matched 35 healthy subjects were included as the control group. Statistical analyses were performed using SPSS 18.0 and P value <0.05 was considered as statistically significant. The patients with RMS had higher WBC count, hsCRP, systolic pulmonary artery pressure (PAPs), left atrial diameter (LAD), IL-17, and IL-23 levels compared to the control subjects. The levels of IL-17 ( P  = 0.012) and IL-23 ( P  = 0.004) were significantly higher in the RMS group. Correlation analysis revealed that IL-17 and IL-23 levels had a significant correlation with each other and with hsCRP and LAD. We demonstrated that serum levels of IL-17 and IL-23 are significantly higher in patients with RMS compared to those of healthy subjects. IL-17 and IL-23 expression may have a possible role in inflammatory processes that result in RMS development.